The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.2196/33314
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of the Use of Digital Contact-Tracing Tools After the COVID-19 Lockdown: Sentiment Analysis and Opinion Mining

Abstract: Background Singapore’s national digital contact-tracing (DCT) tool—TraceTogether—attained an above 70% uptake by December 2020 after a slew of measures. Sentiment analysis can help policymakers to assess public sentiments on the implementation of new policy measures in a short time, but there is a paucity of sentiment analysis studies on the usage of DCT tools. Objective We sought to understand the public’s knowledge of, concerns with, and sentiments on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For instance, in Ref. [44], the authors analysed emotions from the data obtained from the TraceTogether app and conducted a cross-sectional survey at the large public hospital in Singapore after the COVID-19 lockdown.…”
Section: Speech Emotion Recognition (Ser) and Covid-19mentioning
confidence: 99%
“…For instance, in Ref. [44], the authors analysed emotions from the data obtained from the TraceTogether app and conducted a cross-sectional survey at the large public hospital in Singapore after the COVID-19 lockdown.…”
Section: Speech Emotion Recognition (Ser) and Covid-19mentioning
confidence: 99%
“…These insights can inform the development and implementation of similar technologies, promoting effective communication and addressing public concerns in the future. [2] Pelaez (2020) wrote that, In the past decade, the advertising industry has undergone significant advancements in neuroscience, artificial intelligence, and consumer expertise, leading to a greater focus on opinion mining, sentiment analysis, and emotion understanding. These advancements aim to achieve a key advertising objective: delivering relevant advertisements on a large scale.…”
Section: Fig I Sentiment Analysis In Online Product Reviewsmentioning
confidence: 99%
“…According to the study of Pelucio et al [5], which conducted in one of the universities in Brazil for evaluating the presence of depression, and anxiety in university students during Covid-19 pandemic, the results revealed that most of the students reported emotional impact with significant difference of depressive symptoms but no significant difference in anxiety. However, the computer scientist and psychologist can work together in detecting the students feeling by using the opinion mining or the sentiment analyses to study their attitudes and emotions [6]. Therefore, in this study the sentiment analysis of students will be detected and evaluated by developing a chatbot based on supervised learning algorithms, however the corpus in this study is English tweets which classified as positive or negative.…”
Section: Introductionmentioning
confidence: 99%